Nano-scale lithium-silicon alloy material and preparation method and use thereof

By combining polycyclic aromatic compounds with metal lithium and nanosilicon materials in an inert atmosphere, the problem of high preparation costs and difficult to reach the nanoscale scale of existing lithium silicon alloy materials is solved, and the low-cost large-scale preparation of nano-scale lithium silicon alloy materials is achieved and the excellent battery performance is achieved.

CN112038619BActive Publication Date: 2025-05-02LIYANG TIANMU PILOT BATTERY MATERIAL TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202010948797.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2014-01-03
Publication Date
2025-05-02
Estimated Expiration
2034-01-03

AI Technical Summary

Technical Problem

The existing preparation methods for lithium silicon alloy materials have problems such as high cost, complex process, small output and difficult to reach the nanoscale.

Method used

The polycyclic aromatic compound is dissolved in an organic solvent at room temperature in an inert atmosphere to form a precursor solution, metal lithium is added and left to stand, then nanosilicon material is added and stirred, and vacuum drying and filtration is carried out to finally prepare a nano-scale lithium silicon alloy material.

Benefits of technology

It realizes low-cost, simple and easy large-scale preparation of nano-scale lithium-silicon alloy materials, and is suitable for applications such as thermal batteries and lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN112038619B_ABST
    Figure CN112038619B_ABST
Patent Text Reader

Abstract

The invention discloses a nano-scale lithium-silicon alloy material and a preparation method and application thereof. The composition of the nano-scale lithium-silicon alloy material comprises: Li, Si and doping elements; wherein the molar ratio of Li to Si is 1 / 100 to 5 / 1; the total molar content of Li and Si in the nano-scale lithium-silicon alloy material is greater than or equal to 90%; the doping element is one or more of B, C, N, F, Na, Mg, Al, P and Cu; the size of the nano-scale lithium-silicon alloy material in any one dimension is 1 nm to 500 nm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of materials science, and in particular to a nanometer-level lithium-silicon alloy material and a preparation method and application thereof. Background Art

[0002] In thermal batteries, the thermal battery anodes commonly used at present mainly include Li-Al, Li-Si and Li-B alloys. Among them, Li-Al alloy is composed of a single solid solution phase containing 20wt% lithium, so its discharge mechanism is relatively simple and only shows one voltage platform. Li-Si alloy is an anode material with multiple discharge steps. By utilizing the discharge characteristics of Li-Si alloy with multiple voltage platforms, several voltage platforms can be used in the design of thermal batteries. Therefore, its total capacity is larger than that of Li-Al alloy, and its large current discharge capacity is strong. The electrode potential is lower than that of Li-Al alloy, and its comprehensive performance is much better than that of Li-Al alloy. Therefore, thermal batteries using lithium-silicon alloy as negative electrode materials have advantages such as large discharge power, high specific energy, rapid activation, long storage period and compact structure compared with calcium-based and magnesium-based thermal battery systems.

[0003] At the same time, in the current lithium-ion batteries, people have been looking for new high-capacity negative electrode materials. Silicon material is a next-generation lithium-ion battery negative electrode material with great potential. When lithium is embedded in silicon negative electrode materials, lithium and silicon can form a series of alloys, such as Li4.4Si, which has a theoretical capacity of 4200mAh / g. However, the efficiency of silicon negative electrode materials is low in the first week, and the efficiency is not high every week thereafter. A part of lithium can be added to the silicon negative electrode material to form a part of lithium-silicon alloy, so that the lithium loss caused by the formation of the solid electrolyte interface (SEI) film in the lithium-ion battery can be compensated, thereby improving the efficiency and capacity of the lithium-ion battery.

[0004] At present, the commonly used lithium-silicon alloy is usually a lithium-silicon alloy above the micron level. There are two main preparation methods. One is to prepare it by high pressure, such as mixing high-purity lithium powder and silicon powder in a certain proportion and pressurizing at 0.1MPa for 2 hours; the other is to mix the lithium powder and silicon powder evenly and place them in a closed container and sinter them at 550℃ for 200h. However, it should be noted that due to the very high activity of lithium-silicon alloy, it needs to be prepared in a glove box filled with Ar gas, and the oxygen partial pressure and water partial pressure must be strictly controlled to be less than 1ppm and less than 1ppm. Therefore, the preparation cost is high, the process is complicated, the output is low, and it is not suitable for large-scale manufacturing. The lithium-silicon alloy particles prepared by the above two methods are relatively large, basically above the micron level. If a smaller size is required, an effective and safe preparation method has not yet been found. There are also few literature reports on nano lithium-silicon alloy materials in the industry. BRIEF DESCRIPTION OF THE DRAWINGS

[0005] The technical solution of the embodiment of the present invention is further described in detail below through the drawings and examples.

[0006] Figure 1 A flow chart of a method for preparing a nano-scale lithium-silicon alloy material provided in Example 2 of the present invention;

[0007] Figure 2 This is a scanning electron microscope image of the nanoscale lithium-silicon alloy material provided in Example 3 of the present invention;

[0008] Figure 3 A Raman analysis curve diagram of the nano-scale lithium-silicon alloy material provided in Example 3 of the present invention;

[0009] Figure 4 A Raman analysis curve diagram of the nano-scale lithium-silicon alloy material provided in Example 4 of the present invention;

[0010] Figure 5 A Raman analysis curve diagram of the nano-scale lithium-silicon alloy material provided in Example 5 of the present invention;

[0011] Figure 6 This is a Raman analysis curve diagram of the nano-silicon powder provided in Comparative Example 1 of the present invention. Summary of the invention

[0012] The embodiment of the present invention provides a nano-scale lithium-silicon alloy material and a preparation method and use thereof. The nano-scale lithium-silicon alloy material is a nano-scale powdered lithium-silicon alloy material, and its preparation method is simple and easy, low-cost, and can be applied on a large scale. The nano-scale lithium-silicon alloy material provided by the embodiment of the present invention can be used as a negative electrode material for thermal batteries, lithium-ion batteries, lithium-ion capacitors, lithium-sulfur batteries, lithium-air batteries, and all-solid-state batteries.

[0013] In the first aspect, an embodiment of the present invention provides a nanoscale lithium-silicon alloy material, wherein the composition of the nanoscale lithium-silicon alloy material includes: Li, Si and doping elements; wherein the molar ratio of Li to Si is 1 / 100 to 5 / 1; the total molar content of Li and Si in the nanoscale lithium-silicon alloy material is greater than or equal to 90%; the doping elements are one or more of B, Na, Mg, Al, P, and Cu; the size of the nanoscale lithium-silicon alloy material in any one dimension is 1 nm to 500 nm.

[0014] Preferably, the nano-scale lithium-silicon alloy material is a powder, and the specific morphology is one or more of spherical, ellipsoidal, linear, rhombus, cone, rod-shaped and irregular arbitrary polygonal shapes.

[0015] In a second aspect, an embodiment of the present invention provides a method for preparing the nanoscale lithium-silicon alloy material as described in the first aspect, the method comprising:

[0016] At room temperature, in an inert atmosphere, dissolving a polycyclic aromatic compound having a concentration of 0.01 mol / L to 5 mol / L in a first organic solvent to form a precursor solution;

[0017] adding metallic lithium to the precursor solution;

[0018] Standing for 1 to 24 hours, the metallic lithium is dissolved in the precursor solution to form a black, dark green or light yellow lithiated solution; wherein the lithium content in the lithiated solution is 0.001 g / L to 100 g / L;

[0019] Adding doped nano-silicon material to the lithiation solution and continuously stirring for 5 to 100 hours to generate a lithium-silicon alloy suspension;

[0020] After vacuum drying, primary nano-scale lithium-silicon alloy powder is prepared;

[0021] The primary nanometer-scale lithium-silicon alloy powder is washed, filtered and vacuum-dried with a second organic solvent to prepare a nanometer-scale lithium-silicon alloy material.

[0022] Preferably, the method further comprises:

[0023] While the stirring is continued, the lithiated solution to which the doped nano-silicon material is added is heated, and the heating temperature is 50° C. to 100° C.

[0024] Preferably, the nano-silicon material is specifically one or more of silicon nanoparticles, silicon nanotubes and silicon nanosheets with a diameter of 1 nm to 1000 nm.

[0025] Further preferably, the diameter of the nano-silicon material is 20 nm to 200 nm.

[0026] Preferably, the continuous stirring time is 10 to 48 hours.

[0027] Preferably, the metallic lithium is one or more of lithium powder, lithium sheet, lithium rod, lithium strip, and lithium foil.

[0028] Preferably, the polycyclic aromatic compound is one or more of naphthalene, biphenyl, terphenyl, quaterphenyl, anthracene, phenanthrene and their derivatives.

[0029] Preferably, the first organic solvent is one or more of dimethyl ether, diethyl ether, ethylene glycol dimethyl ether, ethylene glycol dibutyl ether, diethylene glycol dibutyl ether, ethylene glycol diethyl ether, propylene glycol dimethyl ether, and propylene glycol diethyl ether.

[0030] Preferably, the second organic solvent is any one of N-methylpyrrolidone, benzene, toluene and xylene.

[0031] In a third aspect, an embodiment of the present invention provides a use of the nanoscale lithium-silicon alloy material as described in the first aspect above, characterized in that the nanoscale lithium-silicon alloy material is used as a negative electrode material for thermal batteries, lithium-ion batteries, lithium-ion capacitors, lithium-air batteries, lithium-sulfur batteries and all-solid-state batteries.

[0032] The nanoscale lithium-silicon alloy material provided in the embodiment of the present invention has a material size of nanoscale, a simple and easy preparation method, low cost, and can be used on a large scale. It can be used as a negative electrode material for thermal batteries, lithium-ion batteries, lithium-ion capacitors, lithium-sulfur batteries, lithium-air batteries, and all-solid-state batteries. DETAILED DESCRIPTION

[0033] The present invention is further described in detail below in conjunction with the embodiments, but it is not intended to limit the protection scope of the present invention.

[0034] Example 1

[0035] Embodiment 1 of the present invention provides a nano-scale lithium-silicon alloy material, comprising: Li, Si and doping elements; wherein the molar ratio of Li to Si is 1 / 100 to 5 / 1; the total molar content of Li and Si is greater than or equal to 50%; the doping elements are one or more of B, C, N, F, Na, Mg, Al, P, and Cu; the size of the nano-scale lithium-silicon alloy material in any one dimension is 1 nm to 500 nm, preferably 20 nm to 200 nm.

[0036] The nano-lithium silicon alloy material can be crystalline or amorphous, in the form of powder, and the microscopic morphology can be one or more of regular shapes such as sphere, ellipsoid, line, rhombus, cone, rod, and irregular arbitrary polygons.

[0037] Preferably, the total molar content of Li and Si is greater than or equal to 95%.

[0038] The nanometer-scale lithium-silicon alloy material provided in this embodiment is a nanometer-scale powdered lithium-silicon alloy material, which can be used as the negative electrode material of thermal batteries, lithium-ion batteries, lithium-ion capacitors, lithium-sulfur batteries, lithium-air batteries and all-solid-state batteries. The battery using it as the negative electrode material has the characteristics of large discharge power, high specific energy, rapid activation, long storage period and compact structure.

[0039] Nano silicon doped with different elements is selected as raw material to prepare doped nano lithium silicon alloy according to the method described in this patent;

[0040] First, the effects of different doping elements on the lithiation effect were evaluated. Then, the obtained doped nano-lithium silicon alloy was assembled with metallic lithium into a button-type half-cell. The reversible capacity at 0.1C, the first efficiency and the relative proportion of the capacity at 3C were tested. The results are shown in Table 1:

[0041] Table 1

[0042]

[0043]

[0044] It can be seen from the results of Table 1 in the above table that the nano lithium silicon alloys obtained by the preparation method of the present invention generally have improved first efficiency and rate performance; from the comparison of the various embodiments, it can be seen that the lithiation effect of the two elements C, N, and F is poor, resulting in an unobvious improvement in the first efficiency of the material and a poor rate performance; the three elements Na Mg Al have good lithiation effects, and the capacity is reduced after doping, but the doping elements improve the conductivity of the material, and the rate performance is greatly improved; and the three elements B, Cu, and P show the best comprehensive performance in the application of nano lithium silicon alloys.

[0045] Example 2

[0046] This embodiment provides a method for preparing a nano-scale lithium-silicon alloy material. Figure 1 As shown, the method includes:

[0047] Step 101, at room temperature, in an inert atmosphere, dissolving a polycyclic aromatic compound having a concentration of 0.01 mol / L to 5 mol / L in a first organic solvent to form a precursor solution;

[0048] Specifically, the polycyclic aromatic compound is one or more of naphthalene, biphenyl, terphenyl, quaterphenyl, anthracene, phenanthrene and their derivatives; the first organic solvent is one or more of dimethyl ether, diethyl ether, ethylene glycol dimethyl ether, ethylene glycol dibutyl ether, diethylene glycol dibutyl ether, ethylene glycol diethyl ether, propylene glycol dimethyl ether and propylene glycol diethyl ether.

[0049] Step 102, adding metallic lithium to the precursor solution;

[0050] The metallic lithium is specifically one or more of lithium powder, lithium sheet, lithium rod, lithium ribbon and lithium foil.

[0051] Step 103, standing for 1 to 24 hours, the metallic lithium is dissolved in the precursor solution to form a black, dark green or light yellow lithiation solution; wherein the lithium content in the lithiation solution is 0.001 g / L to 100 g / L; preferably, the lithium content in the lithiation solution is 1 g / L to 50 g / L.

[0052] Step 104, adding nano-silicon material or doped nano-silicon material to the lithiation solution, and continuously stirring for 5 to 100 hours to generate a lithium-silicon alloy suspension;

[0053] Specifically, during this process, Li in the lithiated solution and Si in the nano-silicon material continuously undergo alloying reactions to generate a lithium-silicon alloy suspension.

[0054] Preferably, in one example, while the continuous stirring is performed, the lithiated solution to which the nano-silicon material or doped nano-silicon material is added is heated, and the heating temperature may be between 30°C and 500°C, preferably between 50°C and 100°C; the alloying reaction time is preferably between 10 and 48 hours. The nano-silicon material may specifically be one or more of silicon nanoparticles, silicon nanotubes and silicon nanosheets with a diameter of 1nm to 1000nm, preferably with a diameter range of 20nm to 200nm. The molar ratio of lithium in the lithiated solution to silicon in the added nano-silicon material may be 100 / 1 to 2 / 1, and more preferably 50 / 1 to 5 / 1. The alloying reaction rate of Li and Si is related to the size of the added nano-silicon, the concentration of the lithiated solution, the reaction temperature and the stirring rate. In addition, heating the lithiated solution can obtain a lithiated solution with high reactivity and shorten the alloying reaction time.

[0055] Step 105, preparing primary nano-scale lithium-silicon alloy powder through vacuum drying;

[0056] Step 106, washing, filtering, and vacuum drying the primary nanometer-scale lithium-silicon alloy powder with a second organic solvent to prepare a nanometer-scale lithium-silicon alloy material.

[0057] Specifically, the second organic solvent is any one of N-methylpyrrolidone, benzene, toluene and xylene.

[0058] The method for preparing the nano-scale lithium-silicon alloy material provided in this embodiment can prepare a nano-scale lithium-silicon alloy material with a size of 1nm to 500nm in any dimension, wherein the molar ratio of Li to Si is 1 / 100 to 5 / 1; the total molar content of Li and Si in the nano-scale lithium-silicon alloy material is greater than or equal to 90%; by adjusting the concentration of the lithiated solution and the molar ratio of the lithium content in the lithiated solution to nano-silicon, nano-scale lithium-silicon alloy materials with different degrees of lithiation can be obtained. The method provided in this embodiment is simple, easy to implement, low-cost, and suitable for applications that can be manufactured on a large scale.

[0059] The following embodiments 3 to 5 are multiple specific examples to illustrate the characteristics of the nano-scale lithium-silicon alloy material prepared by the method provided in the present embodiment 2.

[0060] Example 3

[0061] Embodiment 3 of the present invention provides a first nanoscale lithium-silicon alloy material prepared by the method for preparing the nanoscale lithium-silicon alloy material described in Embodiment 2 above, wherein the molar ratio of lithium and silicon in the lithiated solution to the added nano-silicon material is 5 / 1, the particle diameter of the nano-silicon material is 100 nm, the alloying reaction time is 12 hours, and the reaction temperature is room temperature.

[0062] In this embodiment, the scanning electron microscope photo of the nano lithium silicon alloy material is as follows: Figure 2 As shown. Figure 2 It can be seen that the particle diameter of the nano-scale lithium-silicon alloy material prepared by the preparation method of the nano-scale lithium-silicon alloy material in Example 2 is between 100nm and 600nm. The nano-lithium-silicon alloy material has a certain degree of agglomeration, but the particle size is still maintained at the nanoscale.

[0063] Figure 3 is a Raman analysis curve of the nano-scale lithium-silicon alloy material of this embodiment, Figure 3 It can be seen that the Raman spectrum of the nano-scale lithium-silicon alloy material of this embodiment has obvious amorphization peaks. Compared with Comparative Example 1, in addition to the peaks at 520 cm -1 In addition to the crystalline peak of silicon near 480cm -1 There is an obvious amorphous peak of silicon near 520cm -1 The intensity of the nearby crystalline peak is significantly reduced. The above results show that the lithium in the lithiated solution can indeed be embedded in silicon, causing the silicon to undergo amorphous lithiation reaction.

[0064] Example 4

[0065] Embodiment 4 of the present invention provides a second nanoscale lithium-silicon alloy material prepared by the preparation method of the nanoscale lithium-silicon alloy material described in the above embodiment 2, wherein the molar ratio of lithium and silicon in the lithiated solution to the added nano-silicon material is 5 / 1, the particle diameter of the nano-silicon material is 100 nm, the alloying reaction time is 24 hours, and the reaction temperature is room temperature.

[0066] The Raman analysis results of the prepared nanoscale lithium-silicon alloy material are shown in Figure 4 ,Depend on Figure 4 It can be seen that the Raman spectrum of the nano-scale lithium-silicon alloy material in Example 4 has obvious amorphization peaks. Compared with Comparative Example 1, in addition to the peaks at 520 cm -1 In addition to the crystalline peak of silicon near 480cm -1 There is an obvious amorphous peak of silicon near 520cm -1The intensity of the nearby crystalline peak is significantly reduced. Unlike the nano lithium silicon alloy material in Example 3, the amorphous peak intensity of the nano lithium silicon alloy material in Example 4 is stronger. Therefore, it can be seen that by extending the reaction time, more lithium will enter the silicon to form a nano lithium silicon alloy material.

[0067] Example 5

[0068] Example 5 of the present invention provides a third nano-scale lithium-silicon alloy material prepared by the preparation method of the nano-scale lithium-silicon alloy material described in the above Example 2, wherein the molar ratio of lithium and silicon in the lithiated solution to the added nano-silicon material is 5 / 1, the particle diameter of the nano-silicon material is 100 nm, the alloying reaction time is 12 hours, and the reaction temperature is 60°C.

[0069] The Raman analysis results of the prepared nanoscale lithium-silicon alloy material are shown in Figure 5 ,Depend on Figure 5 It can be seen that the Raman spectrum of the nano-scale lithium-silicon alloy material in Example 5 has obvious amorphization peaks. Compared with Comparative Example 1, in addition to the peaks at 520 cm -1 In addition to the crystalline peak of silicon near 480cm -1 There is an obvious amorphous peak of silicon near 520cm -1 The intensity of the nearby crystalline peak is significantly reduced. Unlike the nano lithium silicon alloy material in Example 3, the amorphous peak intensity of the nano lithium silicon alloy material in Example 5 is stronger. Therefore, it can be seen that by increasing the reaction temperature, more lithium will enter the silicon to form a nano lithium silicon alloy material.

[0070] The following embodiments 6 to 8 are multiple specific examples to illustrate the characteristics of the nano-scale lithium-silicon alloy material prepared by the method provided in the present embodiment 2.

[0071] Example 6

[0072] Example 6 is used to illustrate the dissolution rate of the metal lithium powder described in the present invention in the precursor solution described in Example 2.

[0073] The dissolution rate is represented by slow, medium and fast. The specific dissolution conditions are shown in Table 2.

[0074] Table 2

[0075]

[0076]

[0077] Example 7

[0078] Example 7 is used to illustrate the dissolution rate of the metal lithium foil described in the present invention in the precursor solution described in Example 2.

[0079] The dissolution rate is represented by slow, medium and fast. The specific dissolution conditions are shown in Table 3.

[0080] Table 3

[0081]

[0082] Example 8

[0083] Example 8 is used to illustrate the dissolution rate of the metal lithium foil described in the present invention in the precursor solution described in Example 2.

[0084] The dissolution rate is represented by slow, medium and fast. The specific dissolution conditions are shown in Table 4.

[0085] Table 4

[0086]

[0087] Example 9

[0088] Example 9 is used to illustrate the effect of preparing nano lithium silicon alloy materials using the method in Example 2 of the present invention using different types of aromatic compounds and different types of organic solvents.

[0089] The effect is represented by poor, good, or excellent. The poor effect specifically means that the intensity of the amorphization peak of silicon in the Raman spectrum of the prepared nano-lithium silicon alloy material is less than 500, the moderate effect means that the intensity of the amorphization peak is between 500 and 2000, and the excellent effect means that the intensity of the amorphization peak is greater than 2000.

[0090] The specific effects are shown in Table 5.

[0091] Table 5

[0092]

[0093] Example 10

[0094] Embodiment 10 of the present invention provides a thermal battery prepared based on the nano-scale lithium-silicon alloy material provided in Embodiment 1 above.

[0095] In this embodiment, the negative electrode material of the thermal battery is the nano-scale lithium silicon alloy material provided in Example 1, the electrolyte of the thermal battery is lithium chloride-potassium chloride eutectic, and the positive electrode is one of chromate, metal oxide or sulfide.

[0096] Embodiment 11

[0097] Embodiment 11 of the present invention provides a lithium-ion battery prepared based on the nano-scale lithium-silicon alloy material provided in Embodiment 1 above.

[0098] In this embodiment, the negative electrode material of the lithium-ion battery is the nano-scale lithium-silicon alloy material provided in Example 1. The assembly of the simulated battery is carried out in a glove box containing a high-purity Ar atmosphere, using metallic lithium as the counter electrode and 1 mol of LiPF 6 The solution in EC / DMC was used as the electrolyte to assemble the battery. The constant current charge and discharge test was performed using a charge and discharge instrument produced by Wuhan Landian Electronics Co., Ltd. The discharge cut-off voltage was 0.005V, the charge cut-off voltage was 1V, and the test was performed at a current density of C / 10.

[0099] Example 12

[0100] Embodiment 12 of the present invention provides a lithium-ion battery prepared based on the nano-scale lithium-silicon alloy material provided in Embodiment 1 above.

[0101] In this embodiment, the negative electrode material of the lithium-ion battery is the nanometer-scale lithium-silicon alloy material provided in Example 1, the positive electrode is oxygen, and the electrolyte is an organic electrolyte containing lithium salt.

[0102] Embodiment 13

[0103] Embodiment 13 of the present invention provides a lithium ion capacitor prepared based on the nano-scale lithium-silicon alloy material provided in the above embodiment 1.

[0104] In this embodiment, the negative electrode material of the lithium ion capacitor is the nanometer-scale lithium silicon alloy material provided in Example 1.

[0105] Embodiment 14

[0106] Embodiment 14 of the present invention provides a lithium-sulfur battery prepared based on the nano-scale lithium-silicon alloy material provided in the above embodiment 1.

[0107] In this embodiment, the negative electrode material of the lithium-sulfur battery is the nanometer-scale lithium-silicon alloy material provided in Example 1; the positive electrode active material includes one or several of elemental sulfur, organic sulfide, porous carbon / sulfur composite material, polymer / sulfur composite material, lithium sulfide; the conductive additive includes any one of carbon black, carbon nanotubes, and conductive graphite. The assembly of the simulated battery is carried out in a glove box containing a high-purity Ar atmosphere, using the nanometer-scale lithium-silicon alloy material of the present invention as the counter electrode, and a solution of 5 moles of lithium bis(trifluoromethylsulfonic acid)imide (LiTFSI) in 1,3-dioxolane (DOL) / ethylene glycol dimethyl ether (DME) as the electrolyte to assemble the battery. A constant current charge and discharge mode test is carried out using a charge and discharge instrument, with a discharge cut-off voltage of 1V and a charge cut-off voltage of 3V. The test is carried out at a current density of C / 10.

[0108] Embodiment 15

[0109] Embodiment 15 of the present invention provides an all-solid-state battery prepared based on the nano-scale lithium-silicon alloy material provided in Embodiment 1 above.

[0110] In this embodiment, the negative electrode material of the all-solid-state battery is the nano-scale lithium silicon alloy material provided in Example 1; the positive electrode material is lithium iron phosphate, lithium cobalt oxide, lithium manganate, lithium nickel oxide, lithium manganite, a ternary positive electrode material, and one or any proportion of lithium iron phosphate, lithium cobalt oxide, lithium manganate, lithium nickel oxide, lithium manganite, a ternary positive electrode material coated with a carbon layer, a metal layer, a nitride layer, an oxide layer and a polymer layer; the solid electrolyte is lithium aluminum titanium phosphate or doped lithium aluminum titanium phosphate.

[0111] Comparative Example 1

[0112] The rest is the same as Example 1, except that there is no doping and there is lithiation.

[0113] Comparative Example 2

[0114] This comparative example is used to illustrate the performance of 100 nm nano silicon powder prepared by a traditional method.

[0115] Raman analysis results are as follows Figure 6 As shown by Figure 6 It can be seen that only at 520cm -1 A crystalline peak of silicon appears nearby, and no other impurity peaks appear.

[0116] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for preparing a nano-scale lithium-silicon alloy material, characterized in that: The method comprises: At room temperature, in an inert atmosphere, dissolving a polycyclic aromatic compound having a concentration of 0.01 mol / L to 5 mol / L in a first organic solvent to form a precursor solution; adding metallic lithium to the precursor solution; Standing for 1 to 24 hours, the metallic lithium is dissolved in the precursor solution to form a black, dark green or light yellow lithiated solution; wherein the lithium content in the lithiated solution is 0.001 g / L to 100 g / L; Adding nano-silicon material or doped nano-silicon material to the lithiation solution and continuously stirring for 5 to 100 hours to generate a lithium-silicon alloy suspension; While the stirring is continued, the lithiated solution with the nano-silicon material or the doped nano-silicon material is heated, and the heating temperature is 50° C. to 100° C.; After vacuum drying, primary nano-scale lithium-silicon alloy powder is prepared; The primary nanometer-scale lithium-silicon alloy powder is washed, filtered and vacuum-dried with a second organic solvent to prepare a nanometer-scale lithium-silicon alloy material; The polycyclic aromatic compound is specifically one or more of naphthalene, biphenyl, terphenyl, quaterphenyl, anthracene, phenanthrene and their derivatives; The first organic solvent is specifically one or more of ethylene glycol dimethyl ether, ethylene glycol dibutyl ether, diethylene glycol dibutyl ether, ethylene glycol diethyl ether, propylene glycol dimethyl ether, and propylene glycol diethyl ether; The composition of the nanoscale lithium-silicon alloy material includes: Li, Si and doping elements; wherein the molar ratio of Li to Si is 1 / 100~5 / 1; the total molar content of Li and Si in the nanoscale lithium-silicon alloy material is greater than or equal to 90%; the doping elements are one or more of B, C, F, Na, Mg, Al, P, and Cu; the size of the nanoscale lithium-silicon alloy material in any one dimension is 1nm to 500nm.

2. The method according to claim 1, characterized in that The nano-scale lithium-silicon alloy material is a powder, and the specific morphology is one or more of sphere, ellipsoid, line, rhombus, cone, rod and irregular arbitrary polygon.

3. The method according to claim 1, characterized in that The nano-silicon material is specifically: one or more of silicon nanoparticles, silicon nanotubes and silicon nanosheets with a diameter of 1nm to 1000nm.

4. The method according to claim 1, characterized in that The diameter of the nano-silicon material is 20nm-200nm.

5. The method according to claim 1, characterized in that: The metallic lithium is specifically one or more of lithium powder, lithium sheet, lithium rod, lithium ribbon and lithium foil.

6. The method according to claim 1, characterized in that The second organic solvent is specifically any one of N-methylpyrrolidone, benzene, toluene and xylene.

7. Use of a nano-scale lithium-silicon alloy material prepared by the method according to any one of claims 1 to 6, characterized in that: The nanometer-scale lithium-silicon alloy material is used for negative electrode materials of thermal batteries, lithium-ion batteries, lithium-ion capacitors, lithium-air batteries, lithium-sulfur batteries and all-solid-state batteries.

Citation Information

Patent Citations

  • Reversably removal lithium embedded material for cathode of lithium ion battery and its preparation

    CN1585170A

  • Reagent for lithiation reaction, preparation method and use thereof

    CN1690694A

  • Method of producing prelithiated anodes for secondary lithium ion batteries

    US20100120179A1